Characterisation of Total Electron Content over African region using Radio Occultation observations of COSMIC satellites - Mungufeni, Patrick; Rabiu, Babatunde A; Okoh, Daniel; Jurua, Edward (Elsevier Ltd, 2019)
Abstract This study characterised the Total Electron Content (TEC) over the African region during the years 2008–2015. The TEC data used were the integrated electron density observed during Radio Occultation (RO) event associated with Constellation Observing System for Meteorology, Ionosphere and Climate (COSMIC) satellites. These TEC data were referred to as COSMIC TEC. The results indicate that the COSMIC TEC captures the well known features of the ionosphere such as: (i) occurrence of minimum and maximum TEC during 0:00–08:00 LT and 12:00–16:00 LT respectively, (ii) occurrence of secondary TEC enhancement (maximum) during 16:00–20:00 LT, (iii) lowest TEC values being observed in June solstice and highest TEC values observed in March equinox, (iv) TEC values increase as solar activity changes from low to high, (v) mid latitude TEC values are lower than those of low latitude regions, and (vi) occurrence of equatorial ionisation anomaly. In addition, we validated RO TEC observations of COSMIC satellites using Ground-based Global Navigation Satellite System (GNSS) receiver TEC observations (Ground TEC). To achieve this, we quantified the difference between Ground TEC and COSMIC TEC that were simultaneously observed within the vicinity of the ground receiver. The Upper Quartiles, UQ, of the magnitudes of the differences of coincident COSMIC and Ground TEC over southern mid-latitude regions were <4 TECU, while over low latitude and northern mid-latitude regions, the values ranged from 6.17 to 11.20 TECU. The high TEC differences over low latitude regions compared to those over southern mid latitudes could have resulted from errors due to the spherical symmetry assumption during the RO retrievals. The question that remains is, why there are large TEC differences over the northern mid-latitude regions. Since COSMIC TEC captures the well known features of the ionosphere, it might in future be used for empirical modeling over African region, thus, making this study crucial. _ 2019 COSPAR. Published by Elsevier Ltd. All rights reserved.
Keywords: Ionosphere; Total Electron; Content; COSMIC TEC